Clinical And Pathological Characteristics Of The Fetus And Of The Mother In The Fetal Death At The Maternal Perinatal National Institute. 2011 To 2015. Lima - Peru - Ingar-Pinedo, Jaime (2019)
Objective. To determine the clinical and pathological characteristics of the fetus and from the mother in the fetal death of the NationalMaternal Perinatal Institute from 2011 to 2015. Methodology. This is a quantitative, retrospective, observational, descriptive and crosssectionalstudy. Our population is 954 fetuses that died between week 22 of gestation and / or weight greater than 500 gr at the time of birthat the National Maternal Perinatal Institute from 2011 to 2015. Where our sample is 273 and we apply simple random probabilistic sampling.The technique of data collection that is performed is the observation and the instrument are the records where the data (database andmedical history) that has the National Maternal Perinatal Institute are found. The technique for processing the data will be the SPSS StatisticalBase v22.0 program. In the analysis of data will be estimated by frequency distribution qualitative variables, for quantitative variables will bemeasured measures of central tendency (mean, median) and measures of dispersion (standard deviation).